Challenges in forestry and forest engineering : case studies from four countries in East Europe - Mederski, Piotr S. (Array, 2020)
The forestry and timber industry are strong sectors in the economies of European countries. The current trend of introducing forestry management that respects the various functions of the forest has created new challenges. However, forestry itself, as well as those challenges, varies in different regions in Europe. The aim of this review paper was to describe forest resources and their potential as well to define challenges in forestry and forest engineering in regions of East Europe. Case studies were selected from four countries: Croatia, Latvia, Poland and Romania. The background data and information of the forest-based sector included: forest resources and forest productivity, forest utilisation, development of forest operations and difficulties in forest management. In the analysed countries, state-owned forestry was represented by at least 45%. Forestry is an important sector in all four countries and future challenges are observed in forest management and forest engineering mainly including: an increase in timber resources, improvement in species composition for better productivity and the introduction of effective mechanised forest operations in pre-commercial thinning. Further improvement of harvester heads is expected for the harvesting of broadleaved species and for young stands. Issues linked to the environment were also recognised as challenging factors: mild winters make it difficult to use CTL technology on wet and sensitive sites. Additionally, dry seasons have a high impact on forest fire frequency, but this can be controlled by effective monitoring systems. Improvement in IT systems used in forest operations should limit the carbon footprint by optimising transport, machine use and limiting fuel use. Finally, innovations are recognised as key issues in the improvement of forest management and forest engineering; therefore, special budgets have been allocated to support science and development.